Social innovation and democratic leadership : communities and social changue from below - Parés Franzi, Marc (Libros electrónicos en Ebscohost, 2017)
This book explores new forms of democracy in practice following the 2011 global uprisings; democracy that comes from below, by and for the ?have-nots'. Combining theories of social innovation and collective leadership, it analyses how disadvantaged communities have addressed the effects of economic recession in two global cities: Barcelona and New York.